UNDERNUTRITION AND OBESITY IN PEDIATRIC PATIENTS ADMITTED IN A ROMANIAN HOSPITAL - Cristina Adriana Becheanu; Gabriela Lesanu; Roxana Elena Smadeanu; Iulia Florentina Tincu (Amaltea Medical Publishing House, 2014)
Aims. The determinants of children nutrition status varies around the globe in relation with socio-economic particularities, dietary habits and family lifestyle. The present study attempted to evaluate the changes and determinants of nutritional status of a representative children population from South Romania. Materials and methods. A prospective cross section study was performed in Grigore Alexandrescu Emergency Children's Hospital from Bucharest between December 2010-February 2011. We enrolled 1529 children and anthropometric, dietary assessment and interview schedule were used for all the participants. Study design was similar with the one used in 2005, on similar condition (timing and participants). The population was divided in 2 age groups: 0-2 years and 2-18 years. Data analyze used SPSS software and the Data Analysis module of MICROSOFT EXCEL 2007. Chi-Squared Test was performed for hypothesis testing involving nominal variables (categorical), non-parametric Wilcoxon-Mann-Whitney Test for comparing values of two independent cohorts, Independent Sample T Test for comparing average values of two independent cohorts, and the 'Correlate' function /Pearson coefficient for proving associations between the parameters being considered. Results. The overall rate of undernutrition was 11% while 13% subjects were obese/overweight. Half of subjects with undernutrition came from low-income families. Compared to non-obese children, obese subjects regularly consume sweets and hyper caloric drinks (p<0.001), spend more time watching TV and less time doing physical activity (p<0.001). Comparing data 2005/2011 we revealed that there is a decreasing level of malnutrition for both age groups and there is a warring prevalence of overweight/obese children. Conclusions. Almost a quarter of subject had nutritional status modifi cations. Inappropriate dietary habits (hypercaloric, hyperglucidic) and sedentary lifestyle were the main determinants of overweight/ obesity. This study provides data for national database and it represents an important argue in order to establish children nutritional diseases prevention programs.